The Rhodes Scholarship in the Current Era of Student Activism: What Do We Consider "Prestigious" and Who Benefits?. Issue 3 (2nd July 2016) - Adam, LeAnn
Abstract: Contemporary student activism has revealed deep feelings of alienation on college campuses, prompting strong reactions to current and historical racial injustice, including the history of Cecil Rhodes. Can advisors promote restorative justice by encouraging reflection upon privileges afforded to Rhodes scholars and their responsibility to address society's global problem?